Relationship between job-related tension, negative affect at work and organizational culture - Karamushka, Liudmyla; Tereshchenko, Kira; Kredentser, Oksana; Lazos, Gelena; Karamushka, Taras (Social Welfare: Interdisciplinary Approach, 2019)
This study explores relationships between job-related tension, negative affect at work and organizational culture in educational organizations. It has been found that teaching staff assess job-related tension and negative affect at work higher than educational organization managers do. It also has been shown that power culture contributes to increasing tension in educational organizations, while person culture and task culture as well as the strength of organizational culture contribute to reducing tension and negative affect at work in educational organizations.